Normality, abnormality, and pathology in Merleau-Ponty - Bredlau, Susan; Welsh, Talia (State University of New York Press, 2022)
"Drawing on Merleau-Ponty offers new insights into our understandings of health and illness, ability and disability, and the scientific and cultural practices that both enable and limit our capacity for diverse experiences"-- Provided by publisher.
Keywords: Public health -- Philosophy.; Epidemiology -- Philosophy.; Public health.; Public Health; Santé publique -- Philosophie.; Épidémiologie -- Philosophie.; Santé publique.; public health.; PHILOSOPHY / Movements / Phenomenology.; Epidemiology -- Philosophy; Public health -- Philosophy